2020
DOI: 10.1371/journal.pone.0230125
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous preterm birth and cervical length in a pregnant Asian population

Abstract: Objective Preterm birth (birth before 37 weeks of completed gestation) is the leading cause of neonatal death, and has an incidence of 5-13% which is believed to be on the rise. The objective of this study was to determine the rate of spontaneous preterm birth and investigate the relationship between preterm birth and cervical length in a pregnant Asian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
(32 reference statements)
3
13
0
2
Order By: Relevance
“… 26 A study by Thain et al found a significantly shorter median CL at 28 to 22 weeks and at 28 to 32 weeks in the Indian population compared with the other ethnicities. 27 To the best of our knowledge, no study has been undertaken to evaluate the relation of ethnicity and UCA.…”
Section: Discussionmentioning
confidence: 99%
“… 26 A study by Thain et al found a significantly shorter median CL at 28 to 22 weeks and at 28 to 32 weeks in the Indian population compared with the other ethnicities. 27 To the best of our knowledge, no study has been undertaken to evaluate the relation of ethnicity and UCA.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical length is a key determinant of PTB [ 26 ]. In our meta-analysis, the subgroup analysis revealed that the rates of PTB <37 weeks and PTB <35 weeks were significantly lower in patients who had non-selected cervical length at the time of study inclusion and randomization.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound cervical shortening can be detected weeks before delivery, at about 32 weeks for term births and as early as 16–24 weeks for preterm births [ 2 ]. A study conducted on 934 asymptomatic patients who had serial cervical length measurements performed at 4 antenatal visits showed that there is a significantly shorter cervical length in the 2nd and 3rd trimester in patients who eventually had a preterm birth [ 5 ]. However, the role for cervical length measurements in women with symptoms of PTL remains unclear.…”
Section: Introductionmentioning
confidence: 99%